Validity and Reliability of Conception Diagnostic Test Using Five-Tier Format for Elasticity Concepts (Universitas Negeri Surabaya, 2020)
Abstract Physics is one of subjects taught in secondary high school that potentially causes misconceptions on students. One of them occurs in Elasticity concepts as found by the authors. For example, students assumed that butter, wax and wet clay are elastic objects since it can be shaped easily. This assumption is wrong because those objects are plastic (non-elastic) materials, i.e. when the objects are given an attraction force, the objects will not return to its original form. Therefore, students were considered to experience misconceptions. Such misconceptions should be overcome soon, one of them is by multi-tier diagnostic test. This article aims to develop a conception diagnostic test in five-tier format for Elasticity concepts and to determine the validity (both internal and external aspects) and reliability. Two groups of students were involved: 21 students to gain common reasons (i.e. third-tier questions) and 32 students to collect the validity and reliability data. The internal validity was assessed by a pointed Physics lecturer in UNESA. The external validity covers content and construct aspects. The content validity was determined by false positives (FP) and false negatives (FN) data (each <10%). The construct validity was analyzed using the Pearson Product Moment correlation (rxy). The Reliability (r11) was determined using the Cronbach's Alpha with r11 = 0.42 and 5% significance level. The internal validity data is 91.33%; the FP and FN values ​​are 5.9 and 2.6%, respectively meaning that the developed instrument is valid. The rxy is 0.600> r11 . Therefore this instrument is valid and reliable for use. Keywords: Five-tier diagnostic test, Elasticity concepts, Validity, Reliability Abstrak Fisika merupakan salah satu mata pelajaran yang diajarkan di sekolah menengah atas yang berpotensi menimbulkan miskonsepsi pada peserta didik (PD). Salah satunya terjadi pada konsep Elastisitas seperti yang ditemukan oleh Penulis. Sebagai contoh, PD menyebutkan bahwa mentega, lilin dan tanah liat basah adalah contoh benda-benda yang bersifat elastis sebab ketiga benda tersebut dapat dibentuk dengan mudah. Anggapan tersebut keliru sebab ketiganya tergolong benda plastis (non elastis), yaitu apabila kepada benda-benda tersebut diberi gaya tarik, maka benda tersebut tidak akan kembali ke bentuk semula. Oleh karena itu PD mengalami miskonsepsi. Miskonsepsi seperti itu harus segera diatasi, salah satunya dengan tes diagnostik multi-tier. Artikel ini bertujuan untuk mengembangkan tes diagnostik konsepsi berformat lima tingkat untuk materi Elastisitas dan menentukan validitas (baik aspek internal maupun eksternal) dan reliabilitas tes. Dua kelompok PD terlibat dalam penelitian ini, yaitu 21 PD untuk menjaring alasan yang umum disebutkan oleh PD (pertanyaan three-tier) dan 32 PD untuk memperoleh data validitas (baik aspek internal maupun eksternal) dan reliabilitas tes. Validitas diuji oleh seorang dosen Jurusan Fisika UNESA. Validitas eksternal mencakup aspek konten dan konstruk. Validitas konten ditentukan berdasarkan nilai positif palsu (false positive, FP) dan negatif palsu (false negative, FN), masing-masing harus < 10 %. Validitas konstruk dianalisis menggunakan persamaan korelasi Pearson Product Moment (rxy) . Reliabilitas (r11) ditentukan menggunakan Alpha Cronbach dengan r11 = 0,42 dan taraf signifikan 5%. Data validitas internal = 91,33 %; nilai FP dan FN masing-masing sebesar 5,9 dan 2,6 % yang berarti bahwa tes yang dikembangkan valid. Nilai rxy = 0,600 > r11. Dengan demikian, tes yang telah dikembangakan ini telah valid dan reliabel untuk digunakan. Kata Kunci: Five-tier diagnostic test, Konsep Elastisitas, Validitas, Reliabilitas